2023
DOI: 10.1111/cup.14481
|View full text |Cite
|
Sign up to set email alerts
|

Artificial intelligence and frozen section histopathology: A systematic review

Abstract: Frozen sections are a useful pathologic tool, but variable image quality may impede the use of artificial intelligence and machine learning in their interpretation. We aimed to identify the current research on machine learning models trained or tested on frozen section images. We searched PubMed and Web of Science for articles presenting new machine learning models published in any year. Eighteen papers met all inclusion criteria. All papers presented at least one novel model trained or tested on frozen sectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 36 publications
(73 reference statements)
0
3
0
Order By: Relevance
“…However, cutting additional tissue sections could introduce further bottlenecks when using AI tools for intraoperative assessment. Yet, some prior research has suggested that AI might expedite the decision on when to section blocks 6,21,22 . The prevalence of low‐quality sections can differ among institution, thus influencing their impact.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, cutting additional tissue sections could introduce further bottlenecks when using AI tools for intraoperative assessment. Yet, some prior research has suggested that AI might expedite the decision on when to section blocks 6,21,22 . The prevalence of low‐quality sections can differ among institution, thus influencing their impact.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, some prior research has suggested that AI might expedite the decision on when to section blocks. 6,21,22 The prevalence of low-quality sections can differ among institution, thus influencing their impact. This variability warrants further investigation.…”
Section: Con Clus I On and Per S Pec Tive Smentioning
confidence: 99%
“…Beyond identifying diagnoses via clinical images and electronic health record notes, machine learning techniques are being applied in dermatopathology ( 66 , 67 ). Groups have developed models to classify basal cell carcinoma in digitized Mohs micrographic surgery histology slides to reduce the workload of manually examining these slides ( 68 ).…”
Section: Applications Of Ai In Dermatologymentioning
confidence: 99%